Optimization Procedure of Roller Elements Geometry with Regard to Durability of Spherical Roller Bearings - Jan Steininger; Stefan Medvecky; Robert Kohar; Tomas Capak (Communications - Scientific letters of the University of Zilina, 2020)
The article deals with an optimization procedure of roller elements geometry with regard to durability of spherical roller bearings. The aim of the article is to examine the impact of change of the roller elements inner geometry on durability and reliability of spherical roller bearings; the contact strain along a spherical roller by means of the Finite Element Method at contact points of components of a spherical roller bearing by means of designed 3D parametric models. The most appropriate shape of roller elements inner geometry of a bearing from the standpoint of calculated durability was determined based on results of the contact analyses.